Political conflict, child mental health, and cognitive development - Hendrik Jürges; Alexandra Schwarz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Children living in the occupied Palestinian territories are exposed to poverty as well as continued physical and psychological violence and human rights violations, leading to low levels of mental health compared to children in Western countries. We use test score and survey data on approximately 4,000 students in grades 5 to 9 in the West Bank to study the effect of poor mental health on cognitive development. We show that low cognitive test scores are significantly linked with measures of mental health such as the Birleson depression self-rating scale or the parent-rated Strengths and Difficulties (SDQ) scores also after controlling for a wide range of potential confounders. Using self-reported exposure to potentially traumatizing events related to the Israeli-Palestinian conflict as instruments for the prevalence of mental health problems, we find evidence for a causal link between mental health and cognitive development. Since our estimators identify the effect only for those whose exposure to potentially traumatizing events has impaired their mental health (non-resilient types), we find IV estimates that are substantially larger than OLS estimates. We conclude that physical and psychological violence related to political conflict harms children's mental health and thus impairs their cognitive development. Although in the long run, addressing the underlying causes of the Israeli-Palestinian conflict is preferable, the results of this study call for short-term measures to improve the mental health and thus the cognitive ability of Palestinian children, such as increased availability of psychiatric counseling in schools and communities.
Keywords: O15; J13; I15; 330